Taiwan's National Palace Museum in transition [videorecording]. (Taipei, Taiwan [Government Information Office])
The entire collection of Taiwan's National Museum contains over 650,000 objects of art and serves as a sanctuary for precious masterpieces and the treasure house of human civilization.
The marvelous story of this national treasure's move to Taiwan is testament to the diligent effort by its people to preserve the legacies of human civilization. This story also depicts the museum's 50 years of history in Taiwan, from preservations, to research, to educational outreach program, to digitizing the art collection. Take a peek at the ongoing changes at the museum, such as privatization and active efforts to bring the cultural relics out of the secluded vaults of the palace to the people.
The National Palace Museum's integration with society acknowledges the localization of Taiwanese culture and represents the limitless possibilities of a Taiwan's knowledge-based economy. Incorporating cutting-edge technology with art and through the internet, the museum is able to bring these national treasures out of its protected sanctuary, allowing Taiwan and the world to step, hand-in-hand, into the new millenium
Keywords: Museum -- Taiwan